Status Kesuburan Tanah sebagai Dasar Strategi Pengelolaan Lahan Sawah di Kabupaten Bantul, Indonesia - Siti Maro'ah; Bambang Hendro Sunarminto; Sri Nuryani Hidayah Utami (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2021)
Rice is the main food commodity in Indonesia. The main factor affecting rice productivity is soil fertility. This study aims to determine the soil fertility status of paddy fields in the Bantul Regency. The research was conducted by surveying soil characteristics supported by laboratory analysis. The survey area consists of 4 Land Map Units (LMU) which are made based on the type of soil, where for each LMU 3 soil sampling points are taken. Soil fertility status is represented by Soil Fertility Index (SFI). The results showed that the SFI in Bantul Regency was moderate (0.72). SFI in LMU-1 is moderate (0.70), LMU-2 is moderate (0.71), LMU-3 is high (0.83) and LMU-4 is moderate (0.64). Significant indicators that were positively correlated with SFI were organic C, total N and available K. The management of paddy fields is based on factors related to SFI. The recommended land management for increasing soil fertility is the addition of organic matter in the form of Azolla which can increase the total N and organic C of the soil as well as the application of manure. Proper management of paddy fields can maintain soil fertility and sustainable rice productivity.